Mechanisms of Diuretic Resistance Study: design and rationale. (6th September 2020) - Cox, Zachary L.; Fleming, James; Ivey‐Miranda, Juan; Griffin, Matthew; Mahoney, Devin; Jackson, Keyanna; Hodson, Daniel Z.; Thomas, Daniel; Gomez, Nicole; Rao, Veena S.; Testani, Jeffrey M.
Abstract: Introduction: Diuretic resistance is a common complication impairing decongestion during hospitalization for acute decompensated heart failure (ADHF). The current understanding of diuretic resistance mechanisms in ADHF is based upon extrapolations from other disease states and healthy volunteers. However, accumulating evidence suggests that the dominant mechanisms in other populations have limited influence on diuretic response in ADHF. Additionally, the ability to rapidly and reliably diagnose diuretic resistance is inadequate using currently available tools. Aims: The Mechanisms of Diuretic Resistance (MDR) Study is designed to rigorously investigate the mechanisms of diuretic resistance and develop tools to rapidly predict diuretic response in a prospective cohort hospitalized with ADHF. Methods: Study assessments occur serially during the ADHF hospitalization and after discharge. Each assessment includes a supervised 6‐hour urine collection with baseline blood and timed spot urine collections following loop diuretic administration. Patient characteristics, medications, physical exam findings, and both in‐hospital and post‐discharge HF outcomes are collected. Patients with diuretic resistance are eligible for a randomized sub‐study comparing an increased loop diuretic dose with combination diuretic therapy of loop diuretic plus chlorothiazide. Conclusions: The Mechanisms of Diuretic Resistance Study will establish a prospective patient cohort and biorepository to investigate the mechanisms of diuretic resistance and urine biomarkers to rapidly predict loop diuretic resistance.